VALUASI EKONOMI DAN DAMPAK WISATA ALAM BUKIT SAKURA TERHADAP PEREKONOMIAN MASYARAKAT - Meitry Indriastuti; Fembriarti Erry Prasmatiwi; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The purposes of this study are to explore the travel costs incurred by visitors to Bukit Sakura, the factors that affect the number of tourist visits to Bukit Sakura, the economic value of Bukit Sakura and the impact of Bukit Sakura on the people's economy. The research location was chosen deliberately in Bukit Sakura Nature Tourism. Data collection was carried out in March-July 2020. The method used in this study was a case study with 76 visitor respondents, 15 worker respondents and 8 business unit respondents. The data analysis methods used are travel cost analysis, Poisson regression analysis, economic value calculation, and Keynesian multiplier effect. Travel expenses incurred by visitors to Bukit Sakura tourism are IDR 88,805 per person per visit. The factors that influence the number of visits to Bukit Sakura are the age and cost of the trip. The economic value of Bukit Sakura based on the travel cost method is IDR 13,111,054,718.63. The Income Multiplier Keynesian value is 0.45 while the Income Multiplier Ratio Type 1 value is 2.68 and the value obtained from Income Multiplier Ratio Type 2 is 5.18. The Income Multiplier Keynesian value of 0.45 indicates that Bukit Sakura tourism still has a low economic impact.Key words: economic impacts, economic value, number of visits, and travel costs.